PENGARUH LOKASI DALAM MENENTUKAN PEMBELIAN ULANG MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA RUMAH MAKAN AYAM PEDAS HJ RUPINI DI JEMBER - laili, Fiqrotul; Ediyanto, Ediyanto; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2022)
The purpose of the study was to determine the effect of location in determining repeat purchases through consumer satisfaction as an intervening variable at Hj Rupini's Spicy Chicken Restaurant in Jember. The sampling technique used in this study was simple random sampling with the Slovin formula with a tolerable error rate of 10% as many as 98 people. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that the results of the study are the location has a positive and significant effect on consumer satisfaction, location has a positive and significant effect on repurchase, consumer satisfaction has a positive and significant effect on repurchase, location has a positive and significant effect on Repurchase through customer satisfaction